Media Pop Up Book sebagai Strategi Inovatif untuk Meningkatkan Hasil Belajar Teks Eksplanasi Siswa Kelas VIII MTsN 1 Aceh Utara - Nursari, Isfiana; Aqlima, Delia; Sundana, Lina; Istiqamah, Istiqamah (Medan Resource Center, 2025)
This study investigates the effectiveness of pop-up book media in improving the learning outcomes of eighth-grade students at MTsN 1 North Aceh in understanding explanatory text material. The research was driven by the need to enhance student engagement and comprehension through innovative instructional media. The central research question addresses whether the use of pop-up books can significantly improve students’ academic performance in explanatory texts. Employing a Classroom Action Research (CAR) design, this study utilized both quantitative and qualitative approaches. A total of 25 students participated as subjects. In the first cycle, the average score was 74.16, with 68% of students meeting the minimum competency standard (KKM). In the second cycle, the average increased to 85.32, with 88% of students achieving the standard. These findings indicate a marked improvement in student performance, demonstrating that the integration of pop-up book media is effective in enhancing learning outcomes. The study concludes that pop-up books serve as an engaging and pedagogically valuable tool for teaching explanatory texts in the junior high school context.